Enhanced supercapacitive performance of polyacrylonitrile derived hierarchical porous carbon via hybridizing with MoS2 nanosheets. (August 2021) - Wang, Shunjie; Qin, Can; Feng, Tao; Zhao, Ping; Cheng, Kuan; Zhou, Peng; Li, Zhuoxun; Lin, Zhiying; Liu, Gang
Highlights: Hierarchical porous carbon/MoS2 nanosheets hybrid was prepared from PAN and exfoliated MoS2 nanosheets. Solution-mixing is an efficient approach to prepare hybrid materials. A small amount of MoS2 nanosheets can significantly enhance the capacitive performance of porous carbon. The hybrid-based supercapacitor has high specific capacitance and excellent durability. Abstract: Two-dimensional MoS2 nanosheets are excellent electrode materials for energy storage devices due to their large surface area and high theoretical capacity. Herein, we demonstrate a significant enhancement in the capacitance of polyacrylonitrile (PAN) derived porous carbon by hybridizing with a small amount of MoS2 nanosheets (with MoS2 feeding of 3 wt%). Due to the template effect and electrostatic adsorption of MoS2 nanosheets, orderly arrangements of PAN chains can be induced on the surface of the MoS2 nanosheets, which subsequently deliver to aromatic heterocyclic rings (or pseudo-graphite sheets) through carbonization. The resulted porous carbon/MoS2 nanosheet composite (PAN- d -AC/MoS2 ) exhibits a specific capacitance of 355.5 F g −1, a 88.4% improvement than that of porous carbon without adding MoS2 (PAN- d -AC), at 0.5 A g −1 in a three-electrode system with aqueous electrolyte. Furthermore, due to the further exfoliation of MoS2 nanosheets and thus increasing of surface area, the specific capacitance was further enhanced during the long-term charge/discharge cycles, and reached 148% of the initial value after 20, 000 cycles. Graphical abstract: Image, graphical abstract